A CRITICAL REVIEW OF STUNTING, RISK FACTORS AND PREVENTION ON TODDLERS IN INDONESIA - I Gusti Ayu Mahadewi (Unmas Press, 2021)
WHO states that the issue of stunting occurs in developing countries, including Indonesia. Indonesia has positioned the fifth country with the highest burden of stunting in toddlers. Stunting is a chronic nutritional problem caused by a lack of nutritional intake for a long time. Stunting is a form of malnutrition is characterized by short stature in toddlers. Stunting in toddlers increases morbidity and mortality rate. It can lead to poor intelligence, productivity, degenerative diseases. The purpose of this study is to review risk factors and prevention on stunting toddlers in Indonesia. This study was carried out through a literature study, and then the results of this study was reviewed using the description method. This paper gives an insight into the risk factors and prevention of stunting toddlers in Indonesia. Nutrition is a top national priority in preventing stunting in Indonesia, carried out with a multisectoral approach. Stunting prevention must start long before toddlers is born. and even from adolescence in order to break the chain of stunting in the life cycle. Given the complex risk factors for toddler stunting, public health nutrition lessons need to be included in the school curriculum.